Optical-base pressure sensing ability of Yb3+: Y2Si2O7 nanoparticles - (:unkn) unknown (TechConnect, 2016)
We report the drastic dependence on pressure of the spectral output of Yb3+: Y2Si2O7 nanoparticles under IR excitation. The spectrum obtained at atmospheric pressure consisted of an intense blue band. At low pressure the spectrum changed to a broad optical band. The Y2Si2O7 activated with Yb3+, since they present bright blue, green and white light emission depending on pressure may be useful as optical-based pressure sensors in potential photonic applications.
Keywords: Cooperative emission; Pressure effects; White light